A Statistical Equilibrium Model of Competitive Firms - Albrecht Irle; Mishael Milaković; Simone Alfarano; Jonas Kauschke (Kiel University, Department of Economics, 2008)
We argue that the complex interactions of competitive heterogeneous firms lead to a statistical equilibrium distribution of firms? profit rates, which turns out to be an exponential power (or Subbotin) distribution. Moreover, we construct a diffusion process that has the Subbotin distribution as its stationary probability density, leading to a phenomenologically inspired interpretation of variations in the shape parameter of the statistical equilibrium distribution. Our main finding is that firms? idiosyncratic efforts and the tendency for competition to equalize profit rates are two sides of the same coin.
Keywords: D21; C16; E10; L10; 330; Statistical equilibrium; maximum entropy principle; diffusion process; stochastic differential equation; competition; profit rate; Gewinn; Statistische Verteilung; Wettbewerb; Gleichgewicht; Entropie; Stochastischer Prozess; Industrieökonomik; Theorie